Pembiayaan Istishsna’ dan Implementasinya di Perbankan Syariah - Suaidi, Suaidi; Hakim, Lukmanul (Fakultas Syariah IAIN madura, 2020)
This paper discusses the financing of Istishna ' and some of its accompanying issues in Sharia banking practices in Indonesia. This financing is a sell-based product that is not uncommon to be practiced by Sharia banking today. In this study, can be drawn some conclusions stating that; Firstly, one of the financing based on trading in the form of Bai ' is Istishna ' which is referred to as order contract on an item from Shani ' to Mustashni '; Secondly, on the basis of the ruling Istishna ' is an agreement that can be practiced by banking; Thirdly, in general the implementation of Sharia banking in the community is able to form the construction of housing projects, motorcycle orders, electricity tokens, school buildings, etc.; Fourth, the problem in this Istishna financing is that it is seen in their lack of innovation in field practice, tends to be rigid and unflexible due to short-term financing. In one of the other problems, the difference between landowners and contractors has resulted in inefficiency of the transaction process so that new violations arise for consumers. On the other hand, this product tends to come from the upper class community when the orientation of the banking formation is to settle the community economy evenly and not see due to caste and other proximity factors.